Charge Redistribution Caused by S,P Synergistically Active Ru Endows an Ultrahigh Hydrogen Evolution Activity of S‐Doped RuP Embedded in N,P,S‐Doped Carbon - Liu, Xiaoyu; Liu, Fan; Yu, Jiayuan; Xiong, Guowei; Zhao, Lili; Sang, Yuanhua; Zuo, Shouwei; Zhang, Jing; Liu, Hong; Zhou, Weijia (Advanced science, 2020)
Water splitting for production of hydrogen as a clean energy alternative to fossil fuel has received much attention, but it is still a tough challenge to synthesize electrocatalysts with controllable bonding and charge distribution. In this work, ultrafine S‐doped RuP nanoparticles homogeneously embedded in a N, P, and S‐codoped carbon sheet (S‐RuP@NPSC) is synthesized by pyrolysis of poly(cyclotriphosphazene‐co‐4,4′‐sulfonyldiphenol) (PZS) as the source of C/N/S/P. The bondings between Ru and N, P, S in PZS are regulated to synthesize RuS2 (800 °C) and S‐RuP (900 °C) by different calcination temperatures. The S‐RuP@NPSC with low Ru loading of 0.8 wt% with abundant active catalytic sites possesses high utilization of Ru, the mass catalytic activity is 22.88 times than 20 wt% Pt/C with the overpotential of 250 mV. Density functional theory calculation confirms that the surface Ru (−0.18 eV) and P (0.05 eV) are catalytic active sites for the hydrogen evolution reaction (HER), and the according charge redistribution of Ru is regulated by S and P with reverse electronegativity and electron–donor property to induce a synergistically enhanced reactivity toward the HER. This work provides a rational method to regulate the bonding and charge distribution of Ru‐based electrocatalysts by reacting macromolecules with multielement of C/N/S/P with Ru. Synthesis of electrocatalysts with controllable bonding and charge distribution can optimize charge distribution and phase composition to induce a synergistically enhanced reactivity toward the hydrogen evolution reaction. This work provides a rational method to produce platinum‐like electrocatalysts, and according catalytic active sites are regulated by bonding C/N/S/P in the same molecular structure with Ru.